The generalized path algebras over standardly stratified algebras - Wang, S. (Algebra and Discrete Mathematics, 2006)
In this note, it is proved that the generalized path algebras over standardly stratified algebras are also standardly stratified, and the generalized path algebras over quasi-hereditary algebras are also quasi-hereditary. The ∆−good module categories over these big quasi-hereditary algebras are determined in terms of those of the given algebras.